Analisis Faktor-faktor yang Mempengaruhi Kepuasan Pelanggan Hotel Merpati Urei Faisei Kabupaten Waropen (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
The purpose of this study was to analyze the factors that influence customer satisfaction at Merpati Urei Faisei Hotel, Waropen Regency, associated with the quality of service and hotel facilities. The population in this study were all customers of Merpati Urei Faisei Hotel, Waropen Regency. This study used a sample of 100 respondents who were and had stayed as customers or guests at Merpati Urei Faisei Hotel in the past year, selected using purposive sampling techniques. The data collection technique used in this study was by distributing questionnaires and data analysis using multiple linear regression analysis techniques with the help of SPSS. The results of the study found that customer satisfaction at Merpati Urei Faisei Hotel, Waropen Regency was positively and significantly influenced by the service quality factor of 0.475, the influence of the hotel facility factor of 0.454. This study is expected to increase insight and knowledge about the quality of service and hotel facilities on customer satisfaction.